2008
DOI: 10.1038/jhh.2008.75
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial adipose tissue expression of adiponectin is lower in patients with hypertension

Abstract: Low plasma adiponectin levels are related to a higher risk of development of metabolic and cardiovascular disorders, including hypertension (HT). To date, there have been no studies supporting the relationship between epicardial adipose tissue (EAT) expression of adiponectin and HT. We collected samples of EAT from 116 patients undergoing elective cardiac surgery, mostly for coronary artery bypass grafting (n ¼ 54), valve surgery (n ¼ 49) or both (n ¼ 12). Samples of subcutaneous adipose tissue (SAT) were harv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 44 publications
2
48
0
1
Order By: Relevance
“…This tissue is a source of pro-inflammatory cytokines (6)(7)(8) and contains low levels of adiponectin, an anti-inflammatory adipokine, in patients with CAD (9,10). Moreover, adiponectin expression in EAT decreases in patients with hypertension (11); although its levels are not modified in diabetes (12). These findings suggest that EAT plays an important role in cardiovascular disease and some of its risk factors.…”
Section: Introductionmentioning
confidence: 73%
“…This tissue is a source of pro-inflammatory cytokines (6)(7)(8) and contains low levels of adiponectin, an anti-inflammatory adipokine, in patients with CAD (9,10). Moreover, adiponectin expression in EAT decreases in patients with hypertension (11); although its levels are not modified in diabetes (12). These findings suggest that EAT plays an important role in cardiovascular disease and some of its risk factors.…”
Section: Introductionmentioning
confidence: 73%
“…Adiponectin is considered to be responsible for reduction in inflammation, stimulation of nitric oxide production and consequently for modulation of endothelial cell function. 20,21 Previous studies have demonstrated an independent negative association Abbreviations: c-f PWV, carotid-femoral pulse wave velocity; hs-CRP, high-sensitivity C-reactive protein; SUA, serum uric acid.…”
Section: Discussionmentioning
confidence: 99%
“…Like other adipose tissues, EAT is now recognized as an endocrine organ, and its proximity to myocardium and coronary arteries suggests the possibility of paracrine action on these structures. In fact, in patients with coronary artery disease (CAD) (5,12) and hypertension (32), EAT produces lower levels of the anti-inflammatory adipokine adiponectin and higher levels of the proinflammatory cytokines IL-6 and leptin than does the EAT of non-CAD or nonhypertensive patients undergoing cardiac surgery, whereas the levels of adiponectin in SAT do not differ between hypertensive and nonhypertensive patients (32), and proinflammatory cytokines are higher in the EAT than the SAT of CAD patients (20).…”
mentioning
confidence: 99%